Bauran Pemasaran (Marketing Mix) Bibit Anggur (Vitis Vinifera) Pada Usaha Kebun Anggur Pulo Gebang - Yeni Sari Wulandari (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Indonesia as a tropical country has a wide area and diverse agroclimate so that it can produce various types of fruit including grapes and is a nutritious fruit commodity and has quite high economic value. Pulo Gebang vineyard is a breeding place for grape seeds as a form of effort to improve the farmers' economy. The Pulo Gebang Vineyard Business is managed by the Jakarta wine community under the auspices of the DKI Jakarta province food security, maritime and agriculture agency. A company will be successful or not, is strongly influenced by activities in marketing its products so that it gets maximum profit. In this stage marketing management is needed, so that the company can sell its products at favorable prices at the expected level and can overcome challenges from competitors in marketing. The purpose of this study is to determine the marketing mix that is applied in the marketing activities of the Pulo Gebang Vineyard business. This research is a qualitative research with a descriptive approach. The process of collecting data is done by means of observation, interviews, documentation. Activities to analyze data through three steps, namely data reduction, presentation and drawing conclusions or verification. The descriptive analysis method uses marketing mix analysis, which uses the 7P variable which consists of Product, Price, Place, Promotion, People, Process, and Physical Environment which can be seen from the Pulo Gebang Vineyard business.